Fear‐learning deficits in subjects with fibromyalgia syndrome?. (7th March 2013) - Jenewein, J.; Moergeli, H.; Sprott, H.; Honegger, D.; Brunner, L.; Ettlin, D.; Grillon, C.; Bloch, K.; Brügger, M.; Schwegler, K.; Schumacher, S.; Hasler, G.
Abstract: Background: Fibromyalgia syndrome (FMS) is frequently associated with psychiatric conditions, particularly anxiety. Deficits in contingency learning during fear conditioning have been hypothesized to increase anxiety and, consequently, pain sensation in susceptible individuals. The goal of this study was to examine the relationship between contingency learning and pain experience in subjects with FMS and rheumatoid arthritis (RA). Methods: Fourteen female FMS subjects, 14 age‐matched female RA subjects and 14 age‐matched female healthy controls (HCs) were included in a fear‐conditioning experiment. The conditioned stimulus (CS) consisted of visual signs, the unconditioned stimulus (US) of thermal stimuli. CS− predicted low‐temperature exposure (US), while CS+ was followed by low or high temperature. Results: In the FMS group, only 50% of the subjects were aware of the US–CS contingency, whereas 86% of the RA subjects and all of the HCs were aware of the contingency. CS+ induced more anxiety than CS− in RA subjects and HCs. As expected, low‐temperature exposure was experienced as less painful after CS− than after CS+ in these subjects. FMS subjects did not show such adaptive conditioning. The effects of the type of CS on heart rate changes were significant in the HCs and the aware FMS subjects, but not in the unaware FMS subjects. Conclusions: Contingency learning deficits represent a potentially promising and specific, but largely unstudied, psychopathological factor in FMS. Deficits in contingency learning may increase anxiety and, consequently, pain sensation. These findings have the potential to contribute to the development of novel therapeutic approaches for FMS.